Natural resources and international development - Clawson, Marion (Baltimore; Johns Hopkins Press, 1964)
This book presents the results of forum on the theme of the 1963 RFF forum which was 'The Role O Natural Resources in International Development', consisting ten essays: three on the commodities or group of commodities - agriculture, oil, and fisheries; four focus on resource problem in regions of the world
Includes bibliographies.
gp. 23/01/2019
Loans
Keywords: Natural resources; Economic development; International development